The Critical Success Factors for Entrepreneurial Coaching in South African Business Incubators - Ndlovu-Hlatshwayo, Elona; Msimango-Galawe, Jabulile (Jurnal Maksipreneur, 2023)
This study examines the critical success factors for entrepreneurial coaching in South African business incubators through a qualitative method that involved interviewing 32 participants. The research aimed to identify the factors contributing to successful coaching interventions between coaches and entrepreneurs. The key findings include the importance of demographics, diversity, and cultural intelligence, coaching relational aspects, the coach’s personal attributes, the entrepreneur’s characteristics, the coach’s competence, and coaching elements. The study highlights the need for coaches to possess emotional intelligence, empathy, and a cultural understanding of their coachees. Additionally, the research underscores the significance of coaching programs and methods tailored to the unique needs and characteristics of the entrepreneurs being coached. The study’s findings have significant implications for coaching practitioners and program developers who work with entrepreneurs in South Africa, and it underscores the need for a nuanced and culturally sensitive approach to coaching and mentoring in the context of South African business incubators.